Pandemic Makers: How Citizen Groups Mobilized Resources to Meet Local Needs in a Global Health Crisis. (May 2023) - Browder, Russell E.; Seyb, Stella; Forgues, Angela; Aldrich, Howard E.
The enormous scale of suffering, breadth of societal impact, and ongoing uncertainty wrought by the COVID-19 pandemic introduced dynamics seldom examined in the crisis entrepreneurship literature. Previous research indicates that when a crisis causes a failure of public goods, spontaneous citizen ventures often emerge to leverage unique local knowledge to rapidly customize abundant external resources to meet immediate needs. However, as outsiders, emergent citizen groups responding to the dire shortage of personal protective equipment at the onset of COVID-19 lacked local knowledge and legitimacy. In this study, we examine how entrepreneurial citizens mobilized collective resources in attempts to gain acceptance and meet local needs amid the urgency of the pandemic. Through longitudinal case studies of citizen groups connected to makerspaces in four U.S. cities, we study how they adapted to address the resource and legitimacy limitations they encountered. We identify three mechanisms—augmenting, circumventing, and attenuating—that helped transient citizen groups calibrate their resource mobilization based on what they learned over time. We highlight how extreme temporality imposes limits on resourcefulness and legitimation, making it critical for collective entrepreneurs to learn when to work within their limitations rather than try to overcome them.